P25 Pulmonary rehabilitation quality improvement via a regional network. (12th November 2019) - Morton-Holtham, L; Wells, E; Congleton, J; Bott, J
Abstract : Background: Our region has been running a pulmonary rehabilitation (PR) clinical network since 2010. The aim being to reduce variation in, and improve standards of, care. It provides opportunity for sharing good practice, including around national BTS PR Guidelines and Standards of Care, discussion of challenges, problem solving, and providing a safe space to support quality improvement (QI) and capability building. Clinicians are encouraged and supported to participate in the National Asthma and COPD Audit Programme (NACAP) PR audits, including a collaborative approach with the national PR audit Project Manager and Clinical Lead. Open sharing of data is encouraged. Method: The NACAP 2017 PR snapshot audit data were analysed. Analysis included comparing the mean of key identified outcomes of the region's 15 providers against the national mean (184 providers). The percentage mean for each provider was first calculated individually, before a mean of the findings was calculated as the overall for each metric and area. Thus, percentages stated do not add for the n=enrolled/completed & referred/assessed as these represent the totals of all services. A Mann Whitney U test was utilised due to the non-parametric data and difference in sample sizes between the groups. Results: The region's providers demonstrate a 9% higher mean conversion of referral to assessment rate than national average (76% [5362/7002] vs 67% [42752/68073], p=0.26) and a 7% higher mean completion rate (69% [393/564] vs 62% [4396/7480], p=0.202) (Fig). They also greatly exceed the national average on the number completing a practice walk for tests of exercise tolerance (84% vs 32%) and the number of patients receiving a written programme of exercise at discharge (91% vs 81%). The large difference in sample size between national and the region's providers, along with the limited sample size of the region, contributes to a lack of statistical significance; despite this a meaningful clinical difference is observed.